Identity-Based Key Exchange on In-Vehicle Networks: CAN-FD & FlexRay - Bogdan Groza; Pal-Stefan Murvay (Sensors, 2019)
Security has become critical for in-vehicle networks as they carry safety-critical data from various components, e.g., sensors or actuators, and current research proposals were quick to react with cryptographic protocols designed for in-vehicle buses, e.g., CAN (Controller Area Network). Obviously, the majority of existing proposals are built on cryptographic primitives that rely on a secret shared key. However, how to share such a secret key is less obvious due to numerous practical constraints. In this work, we explore in a comparative manner several approaches based on a group extension of the Diffie−Hellman key-exchange protocol and identity-based authenticated key agreements. We discuss approaches based on conventional signatures and identity-based signatures, garnering advantages from bilinear pairings that open road to several well-known cryptographic constructions: short signatures, the tripartite Diffie−Hellman key exchange and identity-based signatures or key exchanges. Pairing-based cryptographic primitives do not come computationally cheap, but they offer more flexibility that leads to constructive advantages. To further improve on performance, we also account for pairing-free identity-based key exchange protocols that do not require expensive pairing operations nor explicit signing of the key material. We present both computational results on automotive-grade controllers as well as bandwidth simulations with industry-standard tools, i.e., CANoe, on modern in-vehicle buses CAN-FD and FlexRay.